The Influence Of Perceived Benefit And Ease Of Use On Interest In Using The Ovo Digital Wallet - Sianturi, Todung Barita; Panigoro , Aggi Panigoro Sarifiyono; Sabilla Saberina (Journal of Business and Management Inaba, 2023)
This research aims to determine the influence of perceived usefulness and ease of use on interest in using the OVO digital wallet. This research uses associative research methods with data collection through surveys and non-probability sampling techniques. A total of 100 respondents were taken as samples in this research. The data was then analyzed using multiple linear regression analysis for goodness of fit tests such as the t test, f test, and R2. The research results show that perceived usefulness and ease of use have a positive and significant influence on interest in using the OVO digital wallet. These findings indicate that perceived usefulness and ease of use are the factors that most influence interest in using the OVO digital wallet. Apart from that, the appearance of the features also has an important influence on application usage. An attractive appearance can increase consumer satisfaction and encourage further application use. Therefore, companies must continue to innovate to improve the appearance of application features and beautify them. Apart from the display features, the company must issue various promos, discounts and free vouchers to attract consumers to use the OVO digital wallet application. This can increase interest in using the application and strengthen the company's brand image. Apart from that, companies must consider good quality customer service and ensure that the application can always be used smoothly. Overall, this research provides useful information for companies in developing OVO digital wallet applications. By paying attention to perceived benefits, ease of use, feature display, and promotions, companies can increase interest in using the application.